Development and testing of an arecanut harvester cum sprayer - NIMMI RACHEL GEORGE; Preetha T. J; Er. Jayan P. R (Guide) (Tavanur 1998 Department of Farm Power Machinery and Energy)
Development and testing of an arecanut harvester cum sprayer
Development and testing of an arecanut harvester cum sprayer